Alienation of lands for housing development projects: Some emerging legal issues in Malaysia - Md Dahlan, Nuarrual Hilal (2011)
A housing developer needs land to develop it into housing development project.The land which is to be developed into housing development project may be originally owned by the housing developer itself or the developer got it through purchase from interested seller or through alienation of land disposed by the State Authority. The alienation of land is made on the approval of the State Authority the application to alienate land of the applicant housing developers.There are cases whereby the State Authority approved the applications to alienate land to applicant housing developers without taking into consideration, seriously, the capability of the applicant housing developers concerned in carrying out the intended housing development projects and the suitability of the project locations.These incapability and unsuitability, to the extreme cases, may result in the abandonment of housing development projects.The questions are: Why had the State Authority approved the applications to alienate lands to incapable housing developers and alienate unsuitable lands for housing development projects? What are the powers, responsibility and liability of the State Authority in alienating lands to applicant housing developers for housing development projects? This paper discusses the scenarios happening in Malaysia in regard to the powers and responsibilities of the State Authority in alienating lands for housing development projects to applicant housing developers.The method of research are by way of legal case studies of two abandoned housing projects in Malaysia. This paper also identifies the reasons leading to the problems and issues in alienation of lands for housing development projects which had led to the housing abandonment.The purpose of this paper is to identify the weaknesses in the machinery of the State Authority in approving application for alienation of land for housing development projects which might have led to the housing abandonment.In the ending part of this paper, the author suggests certain legal approaches to overcome the problems and issues in the alienation of lands to applicant housing developers for housing development projects by the State Authority in order to avoid housing abandonment.